INTERFERENSI BAHASA ASING DALAM JURNAL LOGIC POLITEKNIK NEGERI BALI - I Nyoman Mandia (Soshum: Jurnal Sosial dan Humaniora, 2014)
Two or more languages are used interchangeably by the same author, it can be said that the language proficiency level in a state of mutual contact. In every language there is a process of mutual contacts between the influence of one language and another language. As a result, there will be interference both oral and written. Interference is an error that is caused by the tendency of getting used pronunciation (utterances) of a language to another language pronunciation unit includes sounds, grammar, and vocabulary. Interference of foreign language in a scientific paper published in the journal Logic State Polytechnic Bali is still quite dominant. This interference occurs because of a lack of mastery of the Indonesian by the writers. In addition, the authors use the term foreign customs so foreign terms with the Indonesia term is regarded as the same thing.